Correlations of morpho-agronomic traits and forage quality properties in diverse red clover (Trifolium pratense L.) collections - Radinović Irena P.; Vasiljević Sanja Lj.; Branković Gordana R. (Journal of Agricultural Sciences (Belgrade), 2022)
Red clover is an important perennial forage legume and a rich source of highly nutritional voluminous forage for livestock feed, which is continuously improved by plant breeding efforts that rely significantly on trait correlation studies. A two-year field trial was conducted at Rimski Šančevi, Novi Sad, Serbia. The aim of this research was to assess correlations of important morpho-agronomic traits and forage quality properties of 46 red clover accessions of diverse origins. The highest Spearman's correlation coefficient (0.97, p<0.01) was found between the branch number and internode number per stem in the first experimental year. The green mass yield and the dry matter yield in both years had very high (0.95, p<0.01) and high (0.86, p<0.01) correlations, respectively. The stem height and internode number per stem had intermediate correlations in both years (0.68, p<0.01, and 0.50, p<0.01, respectively), and stem height exhibited an intermediate correlation with green mass yield (0.57, p<0.01, and 0.62, p<0.01, respectively) and dry matter yield (0.60, p<0.01, and 0.56, p <0.01, respectively) in both years. Thus, the indirect selection for higher plants with higher numbers of internodes per stem may contribute to accomplishing higher yield performance per plant. Although the branch number showed the highest positive correlation (p<0.01) with internode number per stem and an intermediate positive correlation (p<0.01) with stem height, this trait had a low correlation with green mass yield and dry matter yield and cannot be used as a criterion for indirect selection.